Loss and damage attribution - Huggel, Christian; Stone, Dáithí; Auffhammer, Maximilian; Cramer, Wolfgang; Hansen, Gerrit (Nature Climate Change, 2013)
If research on attribution of extreme weather events is to inform emerging climate change policies, it needs to diagnose all of the components of risk.
MAG ID: 2038026258